Sustainable leadership practices among school leaders and their relationship with school climate - Muhammad Hasrizal Abdul Rahim; Mohd Izam Mohd Hamzah; Aida Hanim A. Hamid (Institute of Advanced Engineering and Science, 2024)
Sustainable leadership practices ensure that the mission and vision of a school continue despite changes and challenges. Such a practice can build the capacity of the organization based on the environment, especially in shaping a better school climate. Past studies have found a significant link between school leadership practices and the school climate. However, there has been little discussion about the phenomenal relationship the in rural national secondary school (SMK) context. Hence, this study aimed to identify the level of sustainable leadership practices of principals and their relationship with the school climate in rural SMK in Malaysia. A total of 450 teachers were selected to participate in the study using proportionate random sampling and questionnaires were adopted as the research method. Due to the COVID-19 pandemic and the research population located in rural areas, data were collected through the mail. The findings showed that the level of sustainable leadership practices of the principals was high (M=4.18, SD=0.52), along with a high level of the school climate (M=4.14, SD=0.51). Sustainable leadership practices were also positively associated with school climate (r=0.607, p<0.05). These findings can be used by the Ministry of Education Malaysia to enhance sustainable leadership practices in the national education leaders professional qualifications designed specifically for future school leaders in Malaysia. In this regard, it is hoped that these findings will enrich the literature on sustainable leadership practices and the school climate.